Financial Statement Fraud Detection Using the Fraud Triangle Theory: A Study of an Indonesian Healthcare Company Listed on The Indonesian Stock Exchange In 2021-2023 - Maharani, Shilla; Serly, Vanica; Nelvirita, Nelvirita (Jurnal Eksplorasi Akuntansi, 2025)
This study investigates the influence of the fraud triangle on financial statement fraud, focusing on pressure (financial stability and financial target), opportunity (nature of industry and ineffective monitoring), and rationalization. The research sample comprises healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using a purposive sampling method, 26 healthcare companies were selected for analysis. The study employs logistic regression as the analytical method, incorporating the overall model fit test, Hosmer and Lemeshow test, goodness-of-fit test, and classification matrix analysis. The findings reveal that financial targets and the nature of the industry positively impact financial statement fraud, whereas financial stability, ineffective monitoring, and rationalization do not exhibit significant effects.